EKSISTENSI SASTRA LISAN MAHALABIU BAGI MASYARAKAT BANJAR KALIMANTAN SELATAN - Rustam Effendi (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2012)
This study aims to describe the forms, utterance settings, and functions of mahalabiufor the Banjar community. It employed the qualitative descriptive method. The data were collected through observations and in-depth interviews with informants. The findings are as follows. First, there are two forms of mahalabiu, i.e. (a) humorous stories and (b) short phrases or sentences. Second, the utterance of mahalabiu takes account of two aspects, i.e. (a) spatial, temporal, and situational settings, and (b) the speaker and listener. Third, mahalabiu is effective as a means of maintaining the Banjar language and as a medium of social criticism. The Banjar language in mahalabiu is not much influenced by other local languages or the Indonesian language in terms of the vocabulary and syntax.